BS EN IEC 60966-3-4. Radio frequency and coaxial cable assemblies. Part 3-4. Detail specification for semi-flexible cable assemblies (jumper), Frequency range up to 6GHz, Type 50-141 semi-flexible coaxial cable (23rd April 2021) - British Standards Institution,
No abstract available